2020
DOI: 10.3389/fpls.2020.607029
|View full text |Cite
|
Sign up to set email alerts
|

Exogenous Calcium Alleviates Nocturnal Chilling-Induced Feedback Inhibition of Photosynthesis by Improving Sink Demand in Peanut (Arachis hypogaea)

Abstract: Arachis hypogaea (peanut) is a globally important oilseed crop with high nutritional value. However, upon exposure to overnight chilling stress, it shows poor growth and seedling necrosis in many cultivation areas worldwide. Calcium (Ca2+) enhances chilling resistance in various plant species. We undertook a pot experiment to investigate the effects of exogenous Ca2+ and a calmodulin (CaM) inhibitor on growth and photosynthetic characteristics of peanut exposed to low night temperature (LNT) stress following w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 80 publications
(143 reference statements)
0
30
0
Order By: Relevance
“…Cold weather accounts for serious reductions in crop yield every year, since many agriculturally important crops, including rice ( Oryza sativa ) and peanut, are chilling sensitive and can only be cultivated in tropical or subtropical regions ( Wu et al, 2020 ). Despite the molecular mechanisms of cold-induced reprogramming of gene expression and the metabolite accumulation pattern were extensively studied in model plants ( Hoermiller et al, 2016 ; Jin et al, 2017 ; Pagter et al, 2017 ; Dasgupta et al, 2020 ), only a handful of reports were related to peanut ( Jiang et al, 2020 ; Wu et al, 2020 ; Zhang H. et al, 2020 ). In this study, we attempted to decipher the regulatory mechanisms of peanut in response to cold stress through combining transcriptome with metabolome analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Cold weather accounts for serious reductions in crop yield every year, since many agriculturally important crops, including rice ( Oryza sativa ) and peanut, are chilling sensitive and can only be cultivated in tropical or subtropical regions ( Wu et al, 2020 ). Despite the molecular mechanisms of cold-induced reprogramming of gene expression and the metabolite accumulation pattern were extensively studied in model plants ( Hoermiller et al, 2016 ; Jin et al, 2017 ; Pagter et al, 2017 ; Dasgupta et al, 2020 ), only a handful of reports were related to peanut ( Jiang et al, 2020 ; Wu et al, 2020 ; Zhang H. et al, 2020 ). In this study, we attempted to decipher the regulatory mechanisms of peanut in response to cold stress through combining transcriptome with metabolome analysis.…”
Section: Discussionmentioning
confidence: 99%
“…This is the PSI donor-side regulation by CET for PSI photoprotection ( Suorsa et al, 2012 ). It has been reported that exogenous calcium alleviates nocturnal chilling-induced photo damage by facilitating CET, thereby enhancing the photosynthesis and biomass accumulation of peanut under low nocturnal temperature stress ( Song et al, 2020 ; Wu et al, 2020 ). Additionally, plant dry weight was significantly lowered in the rice PGR 5-knockdown line compared to that of WT, especially under fluctuating light ( Yamori et al, 2016 ).…”
Section: The Function Of Pgr5/pgrl1-mediated Cet In Plantsmentioning
confidence: 99%
“…The bulk of our earth's energy resources is derived from global photosynthetic activity in either recent or ancient times (Vass et al, 2007;Liu et al, 2011;Lambers and Oliveira, 2019;Nawrocki et al, 2019). The normal operation of photosynthesis is inseparable from the participation of light energy, but any excessive high light would impact the photosystem II (PSII), photosystem I (PSI) and the other thylakoid membrane proteins and resulting in photoinhibition and the accumulation of reactive oxygen species (ROS; Foyer and Noctor, 1999;Chaux et al, 2017;Liu, 2020). In the real world, multiple stress episodes affecting growth and development are common (Suzuki et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Under saturated light, CET provides an important photoprotective role for the activity of oxygen evolution complex (OEC) by forming the proton gradient across the thylakoid membrane (?pH) (Huang et al, 2016b), and pmf to protect PSI and PSII via the acidification of thylakoid lumen (Golding et al, 2004;Basso et al, 2020). Chilling leads to photoinhibition in cold-sensitive plants like tobacco, peanut, and cucumber which is mainly related to CET activity (Huang et al, 2016a;Liu, 2020;Song et al, 2020;Wu et al, 2020). At 4 • C, CET plays a photoprotective role in PSI primarily through the acidification of thylakoid lumen (Huang et al, 2017b).…”
Section: Regulating the Photosynthetic Apparatusmentioning
confidence: 99%